Fractal Characterization of Settlement Patterns and Their Spatial Determinants in Coastal Zones - Zhonghao Zhang; Xiaoqin Yang; Rui Xiao (ISPRS International Journal of Geo-Information, 2015)
Using box-counting and spatial regression, this paper analyzes the morphological characteristics of coastal settlement patterns and their spatial determinants, with a case of the Wen-Tai region on the Chinese eastern coast. Coastal settlement patterns, which reflect the interactions between people and the surrounding environment, can indicate the anthropogenic pressure sustained in the coastal zones. Characterization of settlement patterns in coastal zones is definitely needed for coastal management. Results indicate that coastal settlement patterns in the Wen-Tai region present significant fractal characteristics, and exhibit obvious spatial variations. The morphological characteristics of settlement patterns are significantly correlated with the standard deviation value of elevation and slope, as well as percentage of loam soils. In particular, cities with greater relief amplitude, higher slope variability, and higher percentage of loam soils would present more complexity in form. Proximity to roads and rivers are insignificant determinants. Our study contributes to the understanding of the spatial determinants of the morphological characteristics of settlement patterns in coastal zones. We argue that fractal dimension provides a useful tool to facilitate the identification of vulnerability hotspots for coastal studies.